Flexible self‐supporting organic cathode with interface engineering for high‐performance and wide‐temperature sodium‐ion batteries - Lei Wang; Suqiao Fang; Haichao Wang; Qianqian Peng; Yifeng Liu; Hanghang Dong; Hao Yan; Yong Wang; Shulei Chou; Bing Sun; Yao Xiao; Shuangqiang Chen (Carbon Energy)
Abstract Flexible electrode design with robust structure and good performance is one of the priorities for flexible batteries to power emerging wearable electronics, and organic cathode materials have become contenders for flexible self‐supporting electrodes. However, issues such as easy electrolyte solubility and low intrinsic conductivity contribute to high polarization and rapid capacity decay. Herein, we have designed a flexible self‐supporting cathode based on perylene‐3,4,9,10‐tetracarboxylic dianhydride (PTCDA), interfacial engineering enhanced by polypyrrole (PPy), and carbon nanotubes (CNTs), forming the interconnected and flexible PTCDA/PPy/CNTs using polymerization reaction and vacuum filtration methods, effectively curbing those challenges. When used as the cathode of sodium‐ion batteries, PTCDA/PPy/CNTs exhibit excellent rate capability (105.7 mAh g−1 at 20 C), outstanding cycling stability (79.4% capacity retention at 5 C after 500 cycles), and remarkable wide temperature application capability (86.5 mAh g−1 at −30°C and 115.4 mAh g−1 at 60°C). The sodium storage mechanism was verified to be a reversible oxidation reaction between two Na+ ions and carbonyl groups by density functional theory calculations, in situ infrared Fourier transform infrared spectroscopy, and in situ Raman spectroscopy. Surprisingly, the pouch cells based on PTCDA/PPy/CNTs exhibit good mechanical flexibility in various mechanical states. This work inspires more rational designs of flexible and self‐supporting organic cathodes, promoting the development of high‐performance and wide‐temperature adaptable wearable electronic devices.